Islamic Corporate Governance in Social Fund Management Center (PUSPAS): Modernization of Waqf Social Fund Management - Makrufah Hidayah Islamiah; Moh. Nurul Qomar; Arridha Harahap; Athi' Hidayati (Universitas Islam Negeri Sunan Ampel Sunan Ampel, 2023)
Nowadays, problems of social organization include; weaknesses of management and professionalism, operational cost is low, some people consider it is not a good job, and many more. The gap between expectations and the reality of fund management in social organization requires innovative breakthroughs in the governance system with the implementation of Sharia values in it. In this case, the existence of the Social Fund Management Center (PUSPAS) Airlangga University is needed to maintain the pillars of the economy. This research make an analysis of the practice of Islamic Corporate Governance (ICG) at the Social Fund Management Center (PUSPAS) Airlangga University Surabaya. This research used quasi-qualitative methods. This method became part of post-positivism. Result of this research practice of Islamic Corporate Governance in Ailangga University Surabaya had been used tawhid, syura’, ‘adalah, ihtisab, and universality. For futher research, research can investigate in other public or private facility such as ministry office or corporate.